Factors Affecting Grammatical and Lexical Complexity of Long‐Term L2 Speakers' Oral Proficiency. Issue 2 (6th October 2015) - Lahmann, Cornelia; Steinkrauss, Rasmus; Schmid, Monika S.
Abstract: There remains considerable disagreement about which factors drive second language (L2) ultimate attainment. Age of onset (AO) appears to be a robust factor, lending support to theories of maturational constraints on L2 acquisition. The present study is an investigation of factors that influence grammatical and lexical complexity at the stage of L2 ultimate attainment. Grammatical and lexical complexity were assessed in 102 spontaneous oral interviews. Interviewees' AOs ranged from 7 to 17 years old. Multifactorial analyses yielded consistently significant effects of gender and level of education for grammatical and lexical complexity. Additionally, native language use at work was a significant predictor for lexical complexity; conversely, AO did not emerge as a significant factor. We conclude that grammatical and lexical complexity at the stage of L2 ultimate attainment is the result of a complex interplay of variables that are general to language learning and performance rather than L2 specific. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .